Effect of Na Ion on Physioloyical changes of Wheat Grown in Nutrient Solution - Al – Kaisi, W.A.; Hussein, A.J.; Al Arkwiazi, A.L.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experimentes were carried out by using a nutrient solution in the green house of Biology Dept , college of Education (Ibn Al- Haitham , University of Baghdad .) during 2001 -2002 growing season in order to determine the effect of sodium ion, by using four concentrations: (zero , 40,80,120. Mm), to study the appearance and physiological characteristics for two wheat varieties : IP A99 and Al-Kaid according to factorial experiment in completely randomized design for each concentration. The rcsults showed that the fourth concentration (120 Mm) for the Na ion is the most effective one on Leaf area, chlorophyll content, soluble carbohydrates, nitrogen content and protein percentage.        Moreover the result suggested that the variety (IPA99) showed a good durability toward the increase in the concentration of Na ion